Maternal depression and child severe acute malnutrition: a case-control study from Kenya - S. Haithar; M. W. Kuria; A. Sheikh; M. Kumar; A. Vander Stoep (BMC, 2018)
Abstract Background Depression is the leading cause of disease-related disability in women and adversely affects the health and well-being of mothers and their children. Studies have shown maternal depression as a risk factor for poor infant growth. Little is known about the situation in Sub-Saharan Africa. The aim of our study was to examine the association between maternal depression and severe acute malnutrition in Kenyan children aged 6-60 months. Methods A matched case-control study was conducted in general paediatric wards at the Kenyatta National Hospital. The cases were children admitted with severe acute malnutrition as determined by WHO criteria. The controls were age and sex-matched children with normal weight admitted in the same wards with acute ailments. Mothers of the cases and controls were assessed for depression using the PHQ-9 questionnaire. Child anthropometric and maternal demographic data were captured. Logistic regression analyses were used to compare the odds of maternal depression in cases and controls, taking into account other factors associated with child malnutrition status. Results The prevalence of moderate to severe depression among mothers of malnourished children was high (64.1%) compared to mothers of normal weight children (5.1%). In multivariate analyses, the odds of maternal depression was markedly higher in cases than in controls (adjusted OR = 53.5, 95% CI = 8.5-338.3), as was the odds of having very low income (adjusted OR = 77.6 95% CI = 5.8-1033.2). Conclusions Kenyan mothers whose children are hospitalized with malnutrition were shown in this study to carry a significant mental health burden. We strongly recommend formation of self-help groups that offer social support, counseling, strategies to address food insecurity, and economic empowerment skills for mothers of children hospitalized for malnourishment.